2021
DOI: 10.1007/s11664-021-08781-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu Metallic Interlayer Thickness on Optoelectronic Properties of TiO2-Based Multilayers Deposited by DC Pulsed Magnetron Sputtering

Abstract: The effect of interference on the optoelectronic properties of TiO 2 /Cu/TiO 2 multilayers deposited by DC pulsed magnetron sputtering was scrutinized. The TCT multilayers were arranged with different thicknesses of the Cu metallic interlayer. The outcomes revealed that the band gap energy of TiO 2 / Cu/TiO 2 multilayers decreased with increasing Cu metallic interlayer thickness. The E g value for TiO 2 single layer recorded 3.49 eV and decreased to a value of 3.12 eV for the multilayer film deposited with a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The optical spectra (transmittance and reflectance) of the as-deposited and irradiated Sb 40 Se 20 S 40 films over the range of 600–1100 nm are presented in Figure a. The presence of interference fringes in transmittance and reflectance data signifies the homogeneity and uniformity of the films . The increased transmision of the ion-irradiated film could be due to the dissolution of localized states and lattice defects across the bandgap region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical spectra (transmittance and reflectance) of the as-deposited and irradiated Sb 40 Se 20 S 40 films over the range of 600–1100 nm are presented in Figure a. The presence of interference fringes in transmittance and reflectance data signifies the homogeneity and uniformity of the films . The increased transmision of the ion-irradiated film could be due to the dissolution of localized states and lattice defects across the bandgap region.…”
Section: Resultsmentioning
confidence: 99%
“…The optical spectra (transmittance and The presence of interference fringes in transmittance and reflectance data signifies the homogeneity and uniformity of the films. 33 The increased transmision of the ion-irradiated film could be due to the dissolution of localized states and lattice defects across the bandgap region. The increased T may be attributed to a decrease in the number of scattering centers caused by proton ion irradiation.…”
Section: Transmittance (T) Reflectance (R) Absorption Coefficient (α)...mentioning
confidence: 99%
“…It is observed that the k values increased as the wavelength increased for CdO single layer and CdO/Cu/CdO multilayers. Moreover, the k value is increased as the Cu intermetallic layer thickness increased which is recognized to the absorption by free electrons and metallic surface and the effect of surface plasmon generated at the CdO/Cu interface [12].…”
Section: Optical Properties Of Cdo/cu/cdo Multilayers Filmsmentioning
confidence: 99%
“…3 Results and discussion [12,13]. The preferential crystallite orientations in the CdO/Cu/CdO multilayer thin films can be exposed based on the texture coefficient (T c ) using the following equation [14]:…”
Section: Thin Film Characterizationmentioning
confidence: 99%
“…[1][2][3][4] Multilayer films involving metal oxide/ metal/metal oxide were inspected to develop the optoelectronic properties of transparent conducting films comparable to single layer films. Patterns for the functional multilayers are TiO 2 /Cu/TiO 2 , 5,6 ZnO/Ag/ZnO, 7 TiO x /Ag/TiO x , 8 ITO/Cu/ITO, 9 SnO 2 /Cu/SnO 2 , 10 SnO 2 /Ag/SnO 2 , 11 WO 3 /Ag/WO 3 12 and CdO/Cu/CdO. 13 The recompenses characterized by multilayer films than single-layer TCO films are; enhanced durability metal films, small sheet resistance, similar optical transparency in the visible range, and lower film thickness.…”
mentioning
confidence: 99%